Happy life expectancy among older adults: differences by sex and functional limitations - Lima, Margareth G; Belon, Ana Paula; Barros, Marilisa BA (Revista de Saúde Pública, 2016)
OBJECTIVE To evaluate if the happy life expectancy in older adults differs according to sex and functional limitations. METHODS Life expectancy was estimated by Chiang method, and happy life expectancy was estimated by Sullivan method, combining mortality data with the prevalence of happiness. The questions on happiness and limitations came from a health survey, which interviewed 1,514 non-institutionalized older adults living in the city of Campinas, SP, Southeastern Brazil. The happy life expectancy was estimated by sex, age, and functional limitations. Based on the variance and standard error of the happy life expectancy, we estimated 95% confidence intervals, which allowed us to compare the statistical differences of the number of happy years lived among men and women. RESULTS Differences by sex in happy life expectancy were significant at ages 60, 65, and 70. In absolute terms, women live more years happily. But, in relative terms, older men could expect to live proportionally more years with happiness. Happy life expectancy decreased significantly with increasing age in both men and women. Among older people living without functional limitation, differences by sex were statistically significant in all age groups, except at age 80. In the group with limitations, no significant differences by sex were found. Significant differences between the group without and with functional limitations were seen in both men and women. CONCLUSIONS Older men could expect to live a greater proportion of their lives happily in comparison to same-aged women, but women show more years with happiness than men. Functional limitations have a significant impact on happy life expectancy for both sexes.